Obstructive sleep apnea and cognition: insights gleaned from bibliometric analysis - Dong, Jiajia; Yu, Xiao; Wang, Yuxin; Zhang, Honglei; Guo, Rui (Frontiers in Psychiatry, 2023)
Objective Obstructive sleep apnea (OSA) is associated with cognitive impairment. However, the broad trends of the research publications on OSA and cognition are unclear. This study aimed to investigate patterns of research on the relationship between OSA and cognitive function using bibliometric analysis and to identify future research directions by analyzing research trends and emerging hotspots in the field. Methods We searched Web of Science for relevant publications from 2003 to 2022 and conducted a bibliometric analysis of OSA and cognitive research using CiteSpace, R, and VOSviewer. Results A total of 1995 articles met the eligibility criteria for the analysis of OSA and cognition research. There was a notable increase in publications over time, with significant contributions from the United States, particularly Harvard University, leading to substantial academic impact. Gozal D emerged as the most prolific author (59 articles) and influential researcher (3,612 citations) in this field. Hotspot analysis revealed that investigating the pathological physiology and mechanisms of OSA-associated cognitive dysfunction is a recent area of focus, while burst detection analysis identified sleep quality and mild cognitive impairment as top investigation topics. The study by Canessa N published in the American Journal of Respiratory and Critical Care Medicine received the highest number of 77 citations. Conclusion Researchers are increasingly focusing on OSA and cognition. Currently, the majority of studies on OSA-related cognitive dysfunction are focused on correctable aspects of the condition. Future investigations into the pathology of OSA-induced cognitive impairment will facilitate more precise therapeutic interventions.